2015
DOI: 10.3390/ijms17010003
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Alternative Splicing in the Control of Immune Homeostasis and Cellular Differentiation

Abstract: Alternative splicing of pre-mRNA helps to enhance the genetic diversity within mammalian cells by increasing the number of protein isoforms that can be generated from one gene product. This provides a great deal of flexibility to the host cell to alter protein function, but when dysregulation in splicing occurs this can have important impact on health and disease. Alternative splicing is widely used in the mammalian immune system to control the development and function of antigen specific lymphocytes. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 159 publications
(255 reference statements)
0
51
0
1
Order By: Relevance
“…In human, lncRNAs are known to play a major role in gene regulation, including the regulation of alternative splicing and their dysfunction may have an impact on several pathologies and diseases (Fernandes, Acuña, Aoki, Floeter‐Winter, & Muxel, ; Romero‐Barrios, Legascue, Benhamed, Ariel, & Crespi, ). Alternative splicing is prevalent in the mammalian immune system to control lymphocyte homeostasis (Yabas, Elliott, & Hoyne, ). Moreover, lncRNAs regulate the inflammatory response following activation of innate immunity and have been related to autoimmune diseases such as psoriasis (Ahn et al, ; Heward & Lindsay, ).…”
Section: Discussionmentioning
confidence: 99%
“…In human, lncRNAs are known to play a major role in gene regulation, including the regulation of alternative splicing and their dysfunction may have an impact on several pathologies and diseases (Fernandes, Acuña, Aoki, Floeter‐Winter, & Muxel, ; Romero‐Barrios, Legascue, Benhamed, Ariel, & Crespi, ). Alternative splicing is prevalent in the mammalian immune system to control lymphocyte homeostasis (Yabas, Elliott, & Hoyne, ). Moreover, lncRNAs regulate the inflammatory response following activation of innate immunity and have been related to autoimmune diseases such as psoriasis (Ahn et al, ; Heward & Lindsay, ).…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest could be the complex regulation found for several members of the heterogeneous nuclear ribonucleoprotein (hnRNP) complex, RNA-binding proteins involved in downstream gene regulation and G2/M DNA damage checkpoint regulation, apoptosis and immune regulation [38]. hnRNPH1, a protein previously shown as being involved in virus replication [39], was upregulated at day 1 pi with both viruses, overexpression that was maintained for the attenuated E75CV1 virus at day 3 and 7 pi.…”
Section: Table 6 Analysis Of the Canonical Pathways Corresponding To mentioning
confidence: 99%
“…More than 95% of human genes undergo AS [5], implicating a role of this mechanism in all cellular processes. Indeed, AS concerns a vast number of genes involved in many immune system functions, such as T-cell activation and migration, cytokine response, and T-cell homeostasis and apoptosis, all being crucial to prevent the breakdown of self-tolerance and the development of autoimmunity [6,7]. It has been also suggested that AS may increase the immunogenicity of autoantigens by creating novel epitopes that might break the immune tolerance [8].…”
Section: Introductionmentioning
confidence: 99%